Morphology of male World Cup and elite speed climbers - Draga, P.; Baran, P.; Maskell, J. H.; Trybek, P.; Pandurevic, D.; Sutor, A. (Frontiers in Sports and Active Living, 2025)
Aims: To compare somatic characteristics and somatotypes of elite World Cup and national level speed climbers relative to general adult population norms, and to identify anthropometric traits that differentiate performance levels.